Perspectives on software-defined networks: interviews with five leading scientists from the networking community. Issue 1 (August 2015) - Batista, Daniel; Blair, Gordon; Kon, Fabio; Boutaba, Raouf; Hutchison, David; Jain, Raj; Ramjee, Ramachandran; Rothenberg, Christian
Abstract Software defined Networks (SDNs) have drawn much attention both from academia and industry over the last few years. Despite the fact that underlying ideas already exist through areas such as P2P applications and active networks (e.g. virtual topologies and dynamic changes of the network via software), only now has the technology evolved to a point where it is possible to scale the implementations, which justifies the high interest in SDNs nowadays. In this article, the JISA Editors invite five leading scientists from three continents (Raouf Boutaba, David Hutchison, Raj Jain, Ramachandran Ramjee, and Christian Esteve Rothenberg) to give their opinions about what is really new in SDNs. The interviews cover whether big telecom and data center companies need to consider using SDNs, if the new paradigm is changing the way computer networks are understood and taught, and what are the open issues on the topic.